The Effect of Financial Distress on Consumer Non-Cyclical Stock Prices on the Indonesia Stock Exchange In 2019-2021 (E-Jurnal Akuntansi, 2025)
This study aims to analyze the effect of financial distress on the stock prices of manufacturing companies in the consumer non-cyclical sector on the Indonesia Stock Exchange in 2019-2021 using the Altman Z-score model. The number of samples used is 48 companies with non-probability sampling method. Data collection was carried out using a purposive sampling technique with criteria, namely main board consumer non-cyclical sector companies that were actively traded on the IDX in a row during the 2019-2021 period. The acquired data was then subjected to simple linear regression analysis. The study's findings demonstrate that the Z-score status significantly positively affects stock prices, there are also differences in the Z-score status at different times, namely between before and during the COVID-19 pandemic. The implication of this study is the existence of financial distress by using the Altman Z-score analysis as an indicator for investors to consider before investing in a company.
Keywords: Finacnial Disterss; Altman Z-Score; Stock Price